PERAN GURU DALAM MEMBANGUN KECERDASAN EMOSIONAL PESERTA DIDIK SEKOLAH DASAR - Annisa Armadani; Yudhi Arifani (Cerdas Proklamator, 2024)
Emotional intelligence can be defined as the ability to understand, use and manage one's own emotions well. Problems such as laziness, fighting, harsh words, lack of motivation, and even bullying can occur because students cannot control their own emotions. Thus, teachers in developing students' personalities are expected to not only focus on intellectual intelligence but also on students' emotional intelligence. The aim of this research is to describe the role of teachers as models and role models, as mentors, and as advisors in building the emotional intelligence of elementary school students. This research journal was prepared based on data obtained from the field using descriptive qualitative research methods. The data collection was carried out using observation, interviews and documentation of the results of data collection in the field. The data analysis technique uses the Miles and Huberman data analysis model with the steps of data condensation, data0presentation, and drawing conclusions. Based on field data, it can be concluded that teachers play a good role in building students' emotional intelligence as much as possible. Teachers as role models provide good examples in terms of speaking, behaving, dressing, participating in0congregational prayers, high motivation,0and building good relationships with other people. Teachers as mentors accompany and direct students0in routine activities at school, habits such as queuing in the canteen and0throwing out rubbish as well as helping students solve their emotional problems. Teachers as advisors always give good adviceto students who have problems0such as being naughty, fighting, lacking motivation, etc. as well as providing motivation for students who have no problems.